PEMANFAATAN URINE TERNAK DALAM PEMBUATAN PUPUKCAIR UNTUK MENAMBAH NILAI GUNA PADA LIMBAH - Allwar Allwar (UII, 2013)
Utilization of animal urine have been made by the Japanese to be used asfertilizer. In the urine of animals based on research in goat urine already containsNitrogen 36.9 to 37.31%, Phosphate 16.5 to 16.8 ppm, and calcium from 0.67 to 1.27%.This composition is similar to SP-36 fertilizer composition. Based on the research alsotwo (2) kilograms of urea fertilizer the equivalent of 2.5 liters of fertilizer fromfermented goat urine. Based on the averagedata goat / sheep can produce 2.5 liters ofurine per day. Thus, for the farmers and ranchers will be many benefits that can bederived from animal wastes in the form of urine. Farmers can be more independent andto be independent of artificial chemical fertilizers / inorganic. Dusun communityenvironment Sigodog, Purbowono Village, District Kaligesing, Purworejo a lot of peopleraising Etawa. Then this program can also be a step to add value to waste that was in thearea.